Philanthropy in Pesantren: A Review - Uula, Mimma Maripatul; Ali, M. Mahbubi (SMART Insight, 2025)
This study aims to map the development and direction of research on Islamic Boarding Schools & Philanthropy through a bibliometric approach. The research data is sourced from scientific journal publications indexed in the Dimensions database with the keyword